SPATIAL PLANNING FOR RUBBER AND COFFEE DEVELOPMENT IN KONTUM PROVINCE - Nguyễn Duy Liêm; Trần Thị Mỹ Duyên (Tạp chí Khoa học Đại học Đà Lạt)
The study aimed to assess the physical and economic land suitability for perennial agricultural crops (rubber and coffee) in Kontum province using the maximum limitation method of the FAO, cost-benefit analysis and Geographic Information System (GIS). Based on the ecological requirements of each crop and the natural conditions in the study area, the selected land factors were soil type, soil depth, soil texture, elevation, slope, irrigation, rainfall, air humidity, air temperature, the number of dry months, and sunshine hours. The results of the physical land evaluation showed that large parts (> 85%) of the study area were not suitable for rubber and coffee crops. The marginally suitable region for the cultivation of rubber, Robusta coffee, and Arabica coffee were 13%, 10% and 13% of the total evaluation area, respectively. However, the economic land evaluation results showed that most of the marginally physical regions (> 95%) were highly suitable (B/C > 2) for rubber and Robusta coffee, and moderately suitable (1 ≤ B/C ≤ 2) for Arabica coffee. Comparing the land evaluation results with the 2005 current land use map and the coffee/rubber development master plan through 2020 showed that the potential zones for expanding rubber and coffee production in the province are relatively large. Thus, it can be seen that integration of the maximum limitation method of the FAO, cost-benefit analysis and GIS could be useful in quickly and accurately evaluating land for perennial agricultural crops, providing a scientific basis for the rational spatial planning of these crops and acting as a reference to land policy makers and land use planners.